The Influence of Social Media Marketing and Price on Purchase Decision and Repurchase Intention Through Brand Trust Among E-Commerce Consumers in Indonesia - Alvin Ferdiansyah; Munawar Asikin (Economic, Management, Business and Accountancy International Journal, 2025)
The rapid development of e-commerce platforms in Indonesia has transformed consumer purchasing behavior, making social media marketing and price two of the most influential factors in shaping online consumer decisions. This study aims to examine the effect of social media marketing and price on purchase decision and repurchase intention, with brand trust as a mediating variable. Previous research highlights that social media marketing activities such as influencer credibility, content authenticity, informativeness, and interactivity play a crucial role in shaping consumer trust and purchase decision in digital environments. Price perception also significantly determines consumer value assessment and willingness to buy. Brand trust emerges as a key mediator that strengthens consumer confidence, reduces perceived risk, and increases both initial purchase decision and repurchase intention. Using a conceptual model grounded in empirical findings, this study proposes that social media marketing and price positively influence brand trust, which subsequently affects both purchase decision and repurchase intention. This study provides theoretical contributions to consumer behavior research and practical implications for e-commerce marketers in optimizing marketing strategies to enhance customer loyalty.